Vaccine hesitancy and its determinants – a way forward? - Janet Michel; Thomas C Sauter; Marcel Tanner (Journal of Global Health Economics and Policy)
The availability of highly effective SARS-CoV-2 vaccines brought about renewed hope worldwide to overcome the pandemic, becoming an integral part of public health measures. However, vaccine hesitance, defined as the reluctance of people to receive the recommended vaccines, threatens to stand in the way. Understanding why people are not taking up the recommended vaccines can assist in strategy development, which is critical for increasing vaccine uptake. Unfortunately, during the pandemic, social media has often been involved in misinformation and misinterpretation of the scarce research data. This has widened the existing chasms in the society, causing strong polarisation of vaccine-uptaking vs vaccine-hesitant people. Confrontation and stigmatisation can turn hesitance into defiance, and this will have additional detrimental effect. Researchers and medical workers must lead the forefront of honest and respectful communication, acknowledging the concerns that vaccine hesitant people have. This is particularly important as most vaccine hesitant people neither have a political agenda nor are they committed to an anti-scientific cause. Although it may sound trivial, public health needs to revert to its roots of teaching medicine to the people.